R&D Expenditures and Economic Growth Relationship in Turkey - Cuma Bozkurt (International Journal of Economics and Financial Issues, 2014)
In today's world, globalization has reached to such an extent that, investment in information and technology is inevitable to be integrated with global system and increase competitive power. Therefore, R&D investments are of high importance and priority for growth process of economy. This paper investigates the long-run relationship between R&D expenditure and economic growth using the Johansen co-integration and the vector error correction models. The research findings indicate that there is a unidirectional causal relationship running from economic growth to R&D. the long-run coefficients for the variable R&D is strongly statistically significant and has positive value. The growth rate of GDP will increase 0, 2630% if R&D shares in the GDP increases 1%. Keywords: R&D Expenditures; Economic Growth; Turkey; Co-integration JEL Classifications: F43; O32; O30; O40